A Combination of Chemotherapy and Autogenous Vaccine for Control of Bovine Papillomatosis in Cattle - Krishna, Sivarama G.; Haritha, G. S.; Kumar, Prakash B.; Harshini, R.; Geethika, B.; Pooja, R.; Praharshini, N.; Aishwaraya, Lakshmi S. (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during the period from July, 2023 to January, 2024. Two clinical cases of cattle were reported with cutaneous papillomas, one near right umbilical region and another over the right hind teat of cattle. Both the animals were treated with a protocol designed such that it can regulate the secondary bacterial infection, speedy recovery of integument system and enhance the immune response for complete regression of the warts. The innate immune responses of infected animals were augmented with inactivated pathogen associated molecular patterns (PAMPs) as autogenous vaccine candidate. The warts were surgically excised, triturated in sterile PBS, inactivated with 0.5% formaline and prepared the autogenous vaccine. The sterility test of vaccine revealed that the vaccine was free from bacterial and fungal contaminants. The chemotherapy includes the use of drugs Thuja ointment, Inj.Enrofloxacin, Inj.Avil and Inj.Anthiomaline. The dose of the vaccine was 1 ml 20 kg-1 b.wt. subcutaneously and given at weekly intervals for a period of 4 weeks. It was observed that the treatment protocol was successfully effective and regression of warts was noticed from 2nd week onwards. By end of 4th week a complete recovery of the wart infected area was noticed with a black scar left behind. The formalin inactivated autogenous vaccine was effective, and applied for control of bovine papillomavirus infection in cattle with combination of chemotherapeutic drugs resulted in early regression of warts.